PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE BRAINSTORMING UNTUK MENINGKATKAN BERPIKIR KRITIS DI KELAS V SEKOLAH DASAR - Suhirno Suhirno; Hesty Prayekti; Yoga Awalludin Nugraha (Universitas Negeri Surabaya, 2021)
ABSTRACTResearch on this development was intended to produce device learning of a syllabus, lesson plans, sheets of students activity, book students, and tests the ability of think critically students on subjects science class grade 5 second semester. The kind of research this namely research the development of which reference on the model 4D, with stage define, design, development and disseminate. Subject research is the primary school grade 5. Research instruments composed of sheets assessment validity syllabus, lesson plans, sheets of students activity, book students, and tests the ability of think critically. Based on the results they actually obtained (1) syllabus developed valid with a value of 4.10 criteria perfectly valid (2) lesson plans developed valid with a value of 4,25 criteria perfectly valid (3) sheets of students activity developed valid with a value of 4.3 criteria perfectly valid (4) books students who developed valid with a value of 4,25 criteria perfectly valid (5) tests the ability of think critically developed valid with a value of 4.45 criteria perfectly valid. The results of research tests the ability to think critically students obtained the percentage completion of achievement 96,83% the average value of 80.Keywords: device learning, brainstorming, the ability to think critically.ABSTRAKPenelitian pada pengembangan ini bertujuan untuk menghasilkan perangkat pembelajaran yang berupa silabus, rencana pelaksanaan pembelajaran (RPP), lembar kegiatan siswa (LKS), buku siswa, dan tes kemampuan berpikir kritis siswa pada mata pelajaran IPA kelas V semester 2. Jenis penelitian ini yaitu penelitian pengembangan yang mengacu pada model 4D, dengan tahapan Define, Design, Development dan Disseminate. Subyek penelitian adalah siswa-siswi SD kelas V. Instrumen dalam penelitian terdiri dari lembar penilaian validitas silabus, RPP, LKS, buku siswa, dan tes kemampuan berpikir kritis. Berdasarkan hasil penilaian diperoleh (1) silabus yang dikembangkan valid dengan nilai 4,10 dengan kriteria sangat valid. (2) RPP yang dikembangkan valid dengan nilai 4,25 dengan kriteria sangat valid. (3) LKS yang dikembangkan valid dengan nilai 4,3 dengan kriteria sangat valid. (4) Buku siswa yang dikembangkan valid dengan nilai 4,25 dengan kriteria sangat valid. (5) tes kemampuan berpikir kritis yang dikembangkan valid dengan nilai 4,45 dengan kriteria sangat valid. Hasil penelitian untuk tes kemampuan berpikir kritis siswa diperoleh presentase ketuntasan prestasi 96,83% dengan nilai rata-rata 80.Kata Kunci: Perangkat pembelajaran, brainstorming, kemampuan berpikir kritis.